The Effect of The Ratio of Beetroot Juice with Pineapple Core Juice and Carrageenan Concentration from Seaweed (Eucheuma cottonii) on Jelly Candy Quality - Faradiba Hijriani Harahap; Noor Harini; Warkoyo Warkoyo; Rista Anggriani (Food Technology and Halal Science Journal, 2022)
Carrageenan is a gelling agent that can be extracted using coconut water solvent. The ability of carrageenan to form a gel can be applied in various products, such as jelly candy. Beetroot is one of the raw materials that can be used in making jelly candy. Beetroot is known to contain various vitamins and minerals as well as betalain pigments which are very beneficial for the body. The weakness of beetroot is its distinctive aroma and taste that is considered unpleasant. Therefore, the pineapple core was added to reduce it. This research aims to determine the interaction between the ratios of beetroot juice and pineapple core juice with carrageenan concentrations on the quality of jelly candy. This research consisted of two main stages consisted of carrageenan extraction, and followed by application into jelly candy made from the beetroot-pineapple core. This study used a factorial Randomized Block Design (RBD) with first factor (S) the ratio of beetroot juice and pineapple core juice (100%: 0%, 75%: 25%, 50%: 50 %) and second factor (K) concentration of carrageenan (3%, 3.5%, 4%). Parameters observed for the first stage included yield, water content, viscosity, gel strength. Meanwhile, the second stage included water content, ash content, reducing sugar, antioxidant activity, texture, color, and organoleptic (color, aroma, taste, texture). The results showed that there were interactions between treatments on water content, ash content, texture, organoleptic of color, aroma, taste, and texture of jelly candy. The ratio of 50% beetroot juice : 50% pineapple core and 4% carrageenan concentration was known as the best treatment with a water content of 14.79%, ash content 0.72%, reducing sugar 1.81%, antioxidant activity 71.23%, texture 59,6N, brightness (L) 34.53, redness (a+) 0.3, yellowness (b+) 0.83, color 4.2 (attractive), aroma 4 (pleasant) , taste 4.16 (good), texture 3.96 (slightly chewy).